Kinerja Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP)dalam menerbitkan Surat Izin Usaha Perdagangan (SIUP) di Kota Denpasar - Wardani, Ni Putu Kusuma; Yudartha, I Putu Dharmanu; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2020)
ABSTRACT TheeOffice of Investment and One Stop Integrated Services of Denpasar City provides public services to the government in the form of licensing services. The Research objective is to find out the Performance of the One-Stop Investment and The theory uses to analyze theeresults of researchoon theeperformance of the One-Stop Integrated Investment and Service Office in issuing Trade Business Permits in Denpasar is the theory of Mahsun. This research uses descriptive qualitativeemethods with data collectionntechniques such as observation,iinterviews and documentation.nThe results of thissstudy indicate that the Performance of the One-stop Integrated aInvestment and Services Office in issuing a Trading Business License in Denpasar City has not been optimal, which can be seen from several indicators that is process, outputs, outcomes and impacts. Keywords: Performance, Licensing, Trading Business